TRANSPARANSI DAN AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH DI KABUPATEN DELI SERDANG - Yurika Aulia; Deana Sari Br Hasibuan; Hetri Waruwu; Priska Devriska Gulo; Silvia Nurhaliza (Pusat Riset dan Inovasi Nasional, 2024)
This research focuses on providing information regarding transparency and accountability in regional financial management in Deli Serdang Regency in 2022. This research aims to find out how transparent and accountable regional financial management is in Deli Serdang Regency in 2022, as well as to provide a clear picture of management practices regional finance. The research results show that although there have been efforts to increase transparency by providing access to information through websites. Therefore, this research provides recommendations for improving regional financial management practices that are more transparent and accountable, as well as increasing community participation in monitoring regional financial management.